Organizational Communication and Job Insecurity with Work Centrality as a Moderator: A Study on the Impact of COVID-19 Pandemic to Tourism Industry - Putu Yoga Sukma Pratama; Fajrianthi Fajrianthi; Cholichul Hadi (Jurnal Psikologi, 2022)
The economic impact of the Coronavirus Disease (COVID-19) pandemic has left many workers to be laid off. It psychologically caused those with jobs to feel insecure, which is known to affect individuals and organizations negatively. Drawing from Hobfoll’s Conservation of Resources (COR) theoretical framework, this study examined the correlation of organizational communication and job insecurity among workers during the COVID-19 pandemic with the moderating role of work centrality. Data were collected from 271 tourism workers in Bali through the purposive sampling technique. The result showed the negative correlation of organization communication towards job insecurity of tourism workers in Bali. The negative correlation between organizational communication and job insecurity became stronger for Balinese tourism workers with high work centrality than workers with lower work centrality. Accordingly, organizations should make a greater effort to communicate with workers about the organization’s stability during the COVID-19 pandemic to attenuate workers’ job insecurity.